Genome editing in potato via CRISPR-Cas9 ribonucleoprotein delivery - Andersson, Mariette (2018)
Clustered regularly interspaced short palindromic repeats and CRISPR-associated protein-9 (CRISPR-Cas9) can be used as an efficient tool for genome editing in potato (Solanum tuberosum). From both a scientific and a regulatory perspective, it is beneficial if integration of DNA in the potato genome is avoided. We have implemented a DNA-free genome editing method, using delivery of CRISPR-Cas9 ribonucleoproteins (RNPs) to potato protoplasts, by targeting the gene encoding a granule bound starch synthase (GBSS, EC 2.4.1.242). The RNP method was directly implemented using previously developed protoplast isolation, transfection and regeneration protocols without further adjustments. Cas9 protein was preassembled with RNA produced either synthetically or by in vitro transcription. RNP with synthetically produced RNA (cr-RNP) induced mutations, i.e. indels, at a frequency of up to 9%, with all mutated lines being transgene-free. A mutagenesis frequency of 25% of all regenerated shoots was found when using RNP with in vitro transcriptionally produced RNA (IVT–RNP). However, more than 80% of the shoots with confirmed mutations had unintended inserts in the cut site, which was in the same range as when using DNA delivery. The inserts originated both from DNA template remnants from the in vitro transcription, and from chromosomal potato DNA. In 2–3% of the regenerated shoots from the RNP-experiments, mutations were induced in all four alleles resulting in a complete knockout of the GBSS enzyme function.